2021
DOI: 10.3390/foods10112729
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chinese Consumers’ Online Purchase Intentions toward Certified Food Products during the COVID-19 Pandemic

Abstract: The outbreak of COVID-19 has significantly increased consumers’ demands for online groceries, as well as healthy, safe, and better-quality food products. In China, certified food products are commonly perceived as safe and good-quality products. Therefore, this study investigated potential factors that influenced Chinese consumers’ online shopping intentions toward certified food during the COVID-19 crisis. An integrated model was proposed by combining the technology acceptance model (TAM) and the theory of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
(122 reference statements)
1
11
0
Order By: Relevance
“…Regarding the effects of each construct and originating from the primary TPB model on organic food continuous purchase intentions, attitude and PBC were found to positively and significantly influence consumers’ continuous intention to purchase organic food, which supports statements from previous studies [ 27 , 30 , 31 ]. It is worth mentioning that attitude has the most significant impact in both TPB and M-TPB framework, which is inconsistent with prior studies that were conducted during the different pandemic periods; those studies reported that PBC was more effective compared to other constructs [ 37 , 88 ]. One possible explanation for this difference is that the accessibility and convenience were perceived to be more important than buying certified food products by consumers during the early pandemic period.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the effects of each construct and originating from the primary TPB model on organic food continuous purchase intentions, attitude and PBC were found to positively and significantly influence consumers’ continuous intention to purchase organic food, which supports statements from previous studies [ 27 , 30 , 31 ]. It is worth mentioning that attitude has the most significant impact in both TPB and M-TPB framework, which is inconsistent with prior studies that were conducted during the different pandemic periods; those studies reported that PBC was more effective compared to other constructs [ 37 , 88 ]. One possible explanation for this difference is that the accessibility and convenience were perceived to be more important than buying certified food products by consumers during the early pandemic period.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, the intermediary role of attitude in green consumption literature is wellestablished (e.g. Carfora et al, 2021;Qi et al, 2021;Tandon et al, 2020a, b;Zhu et al, 2020). Thus, in relation to H3 and H1 as well as considering Baron and Kenny's (1986) logic (if A influences B and B influences C, then B intermediates the relationship between A and C), we posit that attitude toward EEPE positively mediates the association between subjective norm and EEPE intention.…”
Section: Subjective Normmentioning
confidence: 83%
“…The following questions were asked: “How do you think the overall environmental hygiene of offline markets is?” on a Likert scale fixed at 5 (1 denotes strongly satisfied, 5 denotes strongly dissatisfied) level; “Is fresh food in offline markets safer?”, which was defined as a dummy variable of “0–1” (0 denotes no, 1 denotes yes). Third, we examined the source of respondents’ perceived value of purchasing fresh food online, including the use of online images [ 57 ], online reviews [ 38 ], and the shopping experience [ 58 ]. Some specific problems include: “I relay on the fresh food image to estimate the quality of the food”, “I relay on the other consumers’ comments of fresh foods to estimate”, “I relay on my past experience of purchasing of fresh foods to estimate the quality of foods”.…”
Section: Data and Questionnairementioning
confidence: 99%